The Role and Function of Village Regulations in Regulatory Arrangements in the Field of Village Administration - Marintan Lasrida Sitorus (CV. Era Digital Nusantara, 2025)
Village regulations are vital legal instruments in the administration of autonomous village governments, but their effectiveness is often hampered by the poor quality of drafting and synchronization of regulations. This study aims to examine the role and function of Village Regulations in regulatory reform in the field of village administration through a quasi-experimental approach. Using a Nonequivalent Control Group Design, this study involves an audit of the Regulatory Quality Index (RQI) in villages that received intensive reform interventions compared to a control group. The results show a highly significant difference (p < 0.001) in the improvement of regulatory quality, with the experimental group experiencing an average score increase of 37.24 points compared to the control group, which only increased by 2.23 points. Specifically, regulatory structuring has proven effective in mitigating overlapping norms and strengthening the function of delegating legislation at the local level. In conclusion, strengthening the technical capacity of village legislation is a major causal factor in realizing legal certainty and professional village governance.